Nicotinamide mononucleotide (NMN) protects bEnd.3 cells against H2O2‐induced damage via NAMPT and the NF‐κB p65 signalling pathway. Issue 3 (9th February 2021) - Deng, Xiujun; Liang, Xinghuan; Yang, Haiyan; Huang, Zhenxing; Huang, Xuemei; Liang, Chunfeng; Kuang, Yaqi; Qin, Yingfen; Lin, Faquan; Luo, Zuojie
Abstract : An increasing number of studies have shown that nicotinamide mononucleotide (NMN) can inhibit not only ageing but also oxidative stress and inflammatory reactions by improving energy metabolism. However, the role of NMN in regulating the anti‐apoptotic, antioxidative stress and inflammatory responses of brain microvascular endothelial cells is still unknown. Therefore, here we studied the effects of NMN on H2 O2 ‐induced oxidative damage of bEnd.3 cells. In this study, we found that NMN could inhibit the NF‐κBp65 inflammatory signalling pathway and increase the expression of the enzymes NAMPT, VEGF and eNOS, alleviating H2 O2 ‐induced apoptosis in bEnd.3 cells. Taken together, these results suggest that NMN reduces H2 O2 ‐induced oxidative stress and apoptosis and improves cell functions by inhibiting the NF‐κBp65 inflammatory pathway and increasing NAMPT expression. Abstract : Nicotinamide mononucleotide (NMN) has antioxidant and anti‐apoptosis effects in diabetes and cerebrovascular disease models. We verified that NMN can alleviate the apoptosis of bEnd.3 cells induced by oxidative stress, and we further found that the anti‐oxidation and anti‐apoptosis effects of NMN were related to the regulation of NF‐KBp65 pathway and NAMPT enzyme.